Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1080/13621718.2020.1751404
|View full text |Cite
|
Sign up to set email alerts
|

Tensile-shear fracture behaviour of resistance spot-welded hot stamping sheet steel with Al–Si coating

Abstract: Resistance spot welding (RSW) process with protective coatings on advanced high-strength steels is a challenge. An ultimate tensile strength (UTS)1500 MPa grade hot stamping sheet steel(22MnB5) with Al-Si coating was employed for the RSW process in the present study. The effects of Al-Si coating on the microstructure of RSW joints and tensile-shear fracture behaviour were investigated. Strip-like Fe-(Al,Si) cladding on the surface of nugget tongues acted as the crack source and initiated the fracture. Two type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…RSW is an effective welding process with high productivity owing to low cost and short process time. The coating layers affect resistance spot weldability of HPF steels [23][24][25][26][27][28]. In particular, AlSi-c HPF steels have a wide weldable current range due to their low contact resistance and a large current passage through the melting coating layer [23,29].…”
Section: Introductionmentioning
confidence: 99%
“…RSW is an effective welding process with high productivity owing to low cost and short process time. The coating layers affect resistance spot weldability of HPF steels [23][24][25][26][27][28]. In particular, AlSi-c HPF steels have a wide weldable current range due to their low contact resistance and a large current passage through the melting coating layer [23,29].…”
Section: Introductionmentioning
confidence: 99%
“…Tan et al investigated the effect of Al-Si coating on the tensile shear fracture behavior of the RSW of press-hardened steel grade 22MnB5. They found that Fe-(Al,Si) on the edge of weld nuggets acted as a crack source and imitated the fracture [19]. However, these studies do not compare the tensile shear strength of welded joints between coated and uncoated steel in order to determine the effects of Al-Si coating on the tensile properties of hot-stamped steels.…”
Section: Introductionmentioning
confidence: 99%